Penggunaan Kosakata Serapan Bahasa Jepang (Gairaigo) pada Buku Manual Honda CRV - Saptaji, Hargo; Djaya, Hermansyah (Jurnal Sakura : Sastra, Bahasa, Kebudayaan dan Pranata Jepang; Vol 7 No 1 (2025)DO - 10.24843/JS.2025.v07.i01.p06, 2025)
The Japanese vocabulary is composed of three types: "wago", "kango" and "gairaigo". Currently, foreign words as vocabulary borrowed from foreign languages are more and more easily found in the lives of Japanese people. This can be seen from the large number of Japanese loanwords appearing in various print media in Japan, especially newspapers, magazines and books including car manuals. In this study, the use of loanwords in the Honda CRV manual was analyzed. The purpose of this study is to analyze the usage of loanword vocabulary in Honda CRV manuals where synonyms with other Japanese vocabulary exist and how to classify loanword vocabulary into parts of speech. The research method used is qualitative with a descriptive approach. The data used in this study is mainly data obtained from the Honda CRV manual. As a result of the analysis, 296 loanwords were found. From 296 loanwords, only are synonyms. Then, the vocabulary data by parts of speech shows that there are 286 nouns, verbs and 3 adjective.